(untitled) (REMUNOM, 2025)
Abstract The characteristics intrinsic to the work of the nursing team suggest several adverse conditions and elements that are defined as both physical and psychological burdens on these professionals. Highlighting the occurrence of mental disorders, the present work focuses on mental disorders related to the work of the nursing team. The general objective of the work was to identify the main strategies for minimizing the incidence of mental disorders related to the work of the nursing team. The research methodology is a literature review supported by books and scientific articles published since 2010. The emotional burden of nurses, manifested in stress, anxiety and depression, impacts not only professionals, but also the quality of patient care . Challenges include grueling hours, high-pressure situations and the COVID-19 pandemic. Quantitative data show a high incidence of these symptoms, exacerbated by work overload and lack of mental health policies. Despite this, there are promising initiatives, such as psycho-emotional support programs and improvements in working conditions, highlighting the need for a more comprehensive approach to dealing with this issue. The study highlights the urgency of attention and action to protect the mental health of nursing professionals. In addition to providing individual support, it is essential to address underlying structural causes, such as inadequate working conditions and lack of recognition. Implementing effective policies and ongoing support are essential to ensuring a healthy and sustainable work environment for nurses, allowing them to continue providing quality care to patients. Keywords: Nursing. Mental Disorders. Stress. Depression. Anxiety.